Recent advances of natural fibers based green rubber composites: Properties, current status, and future perspectives. Issue 35 (14th April 2021) - Roy, Kumarjyoti; Debnath, Subhas Chandra; Pongwisuthiruchte, Aphiwat; Potiyaraj, Pranut
Abstract: The searching of suitable alternatives to petroleum‐based fillers is an uncompromising challenge in present day rubber research. Recently, natural fibers are the part of great attention of both academic and industrial researchers due to their easy availability, environmental friendliness, and biodegradability. Natural fiber is cellulose‐rich material, which is preferentially used as alternative filler in rubber technology. This article reviews current advances in natural fibers filled rubber composites in terms of mechanical, thermal, and biodegradable properties (2010–2020). The incorporation of unmodified natural fibers as filler is not able to offer desired reinforcement in rubber composites. Several surface modification methods can be introduced to improve the overall performances of natural fibers filled rubber composites. Finally, the review clarifies present status and future prospects of natural fibers based advanced rubber composites in automobile industry. The successful designing of natural fibers based sustainable rubber composites can introduce a new era in green rubber technology. Abstract :